2002
DOI: 10.1021/ma0204610
|View full text |Cite
|
Sign up to set email alerts
|

Polyimides Derived from Mellophanic Dianhydride

Abstract: The synthesis of mellophanic dianhydride (MPDA), an isomer of pyromellitic dianhydride (PMDA), was studied. A trend of forming cyclic oligomers in the reactions of MPDA with 4,4‘-oxydianiline (ODA) or 4,4‘-methylenedianiline (MDA) in DMAC was found. The cyclic dimer from MPDA/MDA was isolated and fully characterized, including an X-ray crystallographic analysis. The reactions of MPDA with aromatic diamines were found much more complicated than those of PMDA. A model study was performed to clarify the reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 10 publications
2
60
1
Order By: Relevance
“…6 Meanwhile, amorphous PIs derived from non-planar and asymmetrical diamines have also been reported. Yang et al 8 reported that the PIs derived from PMDA and 3-phenyl-1,4-bis(4-aminophenoxy) benzene (p-TPEQ) showed a higher T g at 286 1C in comparison with bis(4-aminophenoxy)benzene-based PI (T g ¼272 1C). 8 Morikawa et al [9][10][11] also reported the preparation and thermal properties of aromatic PIs derived from a series of phenyl groupsubstituted 4,4¢-ODA derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Meanwhile, amorphous PIs derived from non-planar and asymmetrical diamines have also been reported. Yang et al 8 reported that the PIs derived from PMDA and 3-phenyl-1,4-bis(4-aminophenoxy) benzene (p-TPEQ) showed a higher T g at 286 1C in comparison with bis(4-aminophenoxy)benzene-based PI (T g ¼272 1C). 8 Morikawa et al [9][10][11] also reported the preparation and thermal properties of aromatic PIs derived from a series of phenyl groupsubstituted 4,4¢-ODA derivatives.…”
mentioning
confidence: 99%
“…Yang et al 8 reported that the PIs derived from PMDA and 3-phenyl-1,4-bis(4-aminophenoxy) benzene (p-TPEQ) showed a higher T g at 286 1C in comparison with bis(4-aminophenoxy)benzene-based PI (T g ¼272 1C). 8 Morikawa et al [9][10][11] also reported the preparation and thermal properties of aromatic PIs derived from a series of phenyl groupsubstituted 4,4¢-ODA derivatives. Particularly, bis(4-amino-2-biphenyl)ether-based PMDA PI showed significant improvements in solubility in polar aprotic solvents and a higher T g at 303 1C than the aforementioned p-TPEQbased PIs.…”
mentioning
confidence: 99%
“…Yang et al 18,19 reported PIs derived from PMDA and 3-phenyl-1,4-bis(4-aminophenoxy) benzene (p-TPEQ) that showed a higher T g than bis(4-aminophenoxy)-benzene-based PI (T g ¼ 272 1C) at 286 1C. These results show that the pendant phenyl group of p-TPEQ restricts the free rotation of the ether linkage and produces a higher T g because of the expansion of a free rotational unit in the PI chain.…”
Section: Introductionmentioning
confidence: 99%
“…This results in an increase the solubility, a decrease in the complex viscosity, and enhanced T g s due to the rotation-restricted structures [6]. A series of polyimides based on isomeric dianhydrides (such as MPDA, BPDA, BTDA, ODPA, TDPA and HQPDA) have been investigated and the structure-property relationships have been established by different groups [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%